Cloning and physical mapping of the HLA class I region spanning the HLA-E-to-HLA-F interval by using yeast artificial chromosomes. - Geraghty, D E (1992)
The HLA class I genes are located within a 2-million-base pair (2-Mbp) region constituting the telomeric half of the human major histocompatibility complex. The large majority of the class I sequences, including the HLA-A, -E, -F, and -G genes, is found within the telomeric 1 Mbp. We report here the isolation and characterization of yeast artificial chromosome (YAC) clones that span a contiguous region of greater than 1.2 Mbp and include 14 of the 18 characterized class I sequences. Restriction enzyme mapping and the use of locus-specific probes have allowed all of the class I genes and sequences to be ordered and positioned within the region. In addition, the transcriptional orientation of the four class I genes has been determined. Using probes derived from the ends of YAC inserts and from class I pseudogenes, we describe a highly polymorphic region between the HLA-A and HLA-G genes. This region appears to be deleted in certain HLA haplotypes, shortening the distance between HLA-A and HLA-G by greater than 50 kilobase pairs (kbp). As part of the characterization of the YAC clones, unique sequence probes derived from the ends of each YAC insert were identified. When combined with probes derived from HLA genes and pseudogenes, 25 locus-specific probes spanning the 1.2-Mbp region have been identified for an average of 1 probe every 48 kbp.